Atomic-scale oxidation mechanisms of single-crystal magnesium. Issue 48 (3rd December 2019) - Sun, Yong; Wang, Jinming; Guo, Jianxin; Zu, Qun; Huang, Jianyu; Peng, Qiuming
Abstract : Understanding the oxidation process of active metals plays a crucial role in improving their mechanical/oxidation properties. Abstract : Understanding the oxidation process of active metals plays a crucial role in improving their mechanical/oxidation properties. Using in situ environmental transmission electron microscopy and density-functional theory, we firstly clarify the oxidation process of single-crystal Mg at the atomic scale by using a new double-hole technique. A unique incipient interval-layered oxidation mechanism of single-crystal Mg has been confirmed, in which O atoms intercalate through the clean (21̄1̄0) surface into the alternate-layered tetrahedral sites, forming a metastable HCP-type MgO0.5 structure. Upon the increased incorporation of oxygen at the neighboring interstitial sites, the HCP-type Mg–O tetrahedron structure sharply transforms into the FCC-type MgO oxide. In addition, a typical anisotropic growth mechanism of oxides has been identified, wherein it involves two routes: the epitaxial growth of the MgO layer and the inward migration of the MgO/Mg interface. The whole oxidation rate of single-crystal Mg is mostly determined by the inward migration rate of the MgO/Mg interface, which is about six times higher than that of the epitaxial growth rate of the MgO layer along the same orientation planes. Moreover, the inward migration rate of the (020)MgO ‖(011̄0)Mg interface is about twice as large as that of the (200)MgO ‖(0002)Mg interface. This continuous oxide growth is mainly related to the defects in the MgO layer, which builds effective channels for the diffusion of O and Mg atoms. The in situ double-hole observations together with theoretical calculations provide a potential trajectory to probe the oxidation fundamentals of other active metals.